2009
DOI: 10.1109/jlt.2008.2007748
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a Tunable Microwave-Photonic Notch Filter Using Low-Loss Silicon Ring Resonators

Abstract: We present a fully tunable multistage narrowband optical pole-zero notch filter that is fabricated in a silicon complementary metal oxide semiconductor (CMOS) foundry. The filter allows for the reconfigurable and independent tuning of the center frequency, null depth, and bandwidth for one or more notches simultaneously. It is constructed using a Mach-Zehnder interferometer (MZI) with cascaded tunable all-pass filter (APF) ring resonators in its arms. Measured filter nulling response exhibits ultranarrow notch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
90
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(90 citation statements)
references
References 13 publications
(16 reference statements)
0
90
0
Order By: Relevance
“…While this is difficult to achieve with all-electronic filters [3][4][5][6][7], integrated microwave photonic (IMWP) filters [8] can readily achieve multi-gigahertz tuning range without significant degradation in their frequency response. However, these filters typically exhibit limited resolution (GHz instead of MHz linewidths) and are plagued by trade-offs between key parameters, such as between the frequency tuning range and the resolution for multi-tap filters [9][10][11][12][13]; or between the peak rejection and the resolution for resonator-based filters [14][15][16][17][18].Stimulated Brillouin scattering (SBS) [19][20][21][22] offers a route to MHz-resolution IMWP filters. Although SBS has been widely studied in optical fibers, recently there has been a growing interest in harnessing SBS in nanophotonic waveguides [22][23][24][25][26][27].…”
mentioning
confidence: 99%
“…While this is difficult to achieve with all-electronic filters [3][4][5][6][7], integrated microwave photonic (IMWP) filters [8] can readily achieve multi-gigahertz tuning range without significant degradation in their frequency response. However, these filters typically exhibit limited resolution (GHz instead of MHz linewidths) and are plagued by trade-offs between key parameters, such as between the frequency tuning range and the resolution for multi-tap filters [9][10][11][12][13]; or between the peak rejection and the resolution for resonator-based filters [14][15][16][17][18].Stimulated Brillouin scattering (SBS) [19][20][21][22] offers a route to MHz-resolution IMWP filters. Although SBS has been widely studied in optical fibers, recently there has been a growing interest in harnessing SBS in nanophotonic waveguides [22][23][24][25][26][27].…”
mentioning
confidence: 99%
“…Unlike previously reported RF notch filters based on ring resonator with multi-GHz isolation bandwidth and shallow peak rejection [13][14][15], our filter achieved a comparable resolution and peak rejection to state-of-the-art RF notch filters. The enabling signal processing concept reported here is applicable to a wide range of optical filters, such as fiber-Bragg gratings (FBGs) or active filters such as SBS, and will potentially lead to creation of very high performance integrated MWP notch filters in the future.…”
Section: Discussionmentioning
confidence: 60%
“…In the former approach, the RF sidebands in the modulated optical spectrum are directly filtered by means of optical filters with the desired filter shape, and then optical detection results in a consistent transfer of this filter shape to the RF output. As illustrated in Figure 2B, both SSB and DSB modulation can be employed, with only DSB modulation requiring optical filtering to the two sidebands in a mirror-symmetric manner with respect to the optical carrier frequency [52]. In the latter approach, both sidebands are generated via DSB or ASB modulation and also pass through optical filters.…”
Section: System Architecturementioning
confidence: 99%
“…For the integrated microwave photonic implementation of coherent filters, both approaches in Figure 2, that is, filter shape transfer and filter shape synthesis, have been demonstrated. As a salient example for such a filter shape transfer approach, Rasras et al [52] demonstrated an RF notch filter using an RAMZI comprising a four-ring resonator-assisted symmetric MZI with a total chip area of 1.75 mm 2 and an RR FSR of 43 GHz. This work demonstrated a notch depth >30 dB, a 3-dB bandwidth <1 GHz, a tuning range >15 GHz, and the capability of multiple notches at the same time.…”
Section: Coherent Filtersmentioning
confidence: 99%